Hubungan Motivasi Kerja dan Sistem Pengembangan Pegawai Terhadap Kinerja Pegawai di Koperasi Dharmayukti Pengadilan Tata Usaha Negara Palembang - Wendy Liana (Jurnal Ilmiah Ekonomi Global Masa Kini)
Employees are the most important assets in an agency, so that quality improvement needs to be an important concern in an effort to achieve agency goals effectively and efficiently. In every management activity, efforts should be made to align the goals of employees so that in the end the objectives of the agency can be achieved as much as possible. Performance appraisal is the most reliable tool for managers to control human resources and productivity. Performance appraisal can be used effectively in directing employee behavior, in order to produce high quality and volume of human resources. Managers can use the operational performance process to set the direction of work in selecting, training, guiding career planning, and rewarding competent employees. The essence of employment is basically regulation, potential mobilization, motivation process, and human resource development in fulfilling satisfaction through his work. This is useful for achieving the goals of the individual, organization, or community in which he works. Decisions made regarding manpower are strongly influenced by the philosophy adopted by the leader regarding labor empowerment. For example, views on work motivation, and the concept of labor. From this point of view, an employment pattern will be formed that is adjusted to the image of the leader. Every government and private agency will always try to improve the effectiveness of employees' work. This can be done by developing employee work. Most leaders are very supportive of employee development. The lower the job level, the more labor supply there is. The positions leading to special skills are not filled because of the lack of employees who meet the requirements. A person is trained to carry out the basic arrangements essential for the job, the most common types of training being fieldwork, meetings or discussions.